Roll motion characteristics of a polar research ship with ice accumulation in beam waves - Jianzhang Qi; Wei Chai; Jun Wu; Meng Cui; Boao Cai; Li Zhou (International Journal of Naval Architecture and Ocean Engineering)
Stability of polar vessels could be deteriorated due to ice accumulation, making it crucial to investigate the dynamic behavior of the vessel under harsh polar conditions. In this work, the effect of ice accumulation on the roll motion characteristics of a polar research vessel subjected to beam waves has been systematically investigated. Initially, an icing prediction model that integrates environmental factors and hull segmentation is utilized to quantitatively assess ice accumulation across various and durations. Following this, mathematical models of roll motion in regular and random beam waves, based on a one-degree-of-freedom (1-DOF) system, are developed, incorporating nonlinear hydrodynamic terms and parameter variations caused by ice accumulation. Computational fluid dynamics (CFD) simulations are performed to model the free roll decay motion of the ship under durations of ice accumulation ranging from 0 to 24 h, allowing for an in-depth analysis of how ice accumulation affects linear and nonlinear roll damping. Based on these results, ship roll response in regular beam waves is simulated, quantifying the impact of ice accumulation on the roll resonance curve and amplitude bifurcation phenomena. The findings reveal that ice accumulation markedly decreases the linear damping while increasing the nonlinear damping, leading to a shift in the roll resonance frequency toward lower values. This shift broadens the resonance and instability regions of the roll response. Ice accumulation generally amplifies ship roll, but at specific wave periods reduces roll amplitude by shifting the resonance point. These findings advance roll dynamics understanding and reveal instability risks for ice-affected polar vessels.